Ten-year trends in health-related quality of life after surgical and conventional treatment for severe obesity: the SOS intervention study - Karlsson, J; Taft, C; Ryden, A; Sjostrom, L; Sullivan, M (International Journal of Obesity, 2007)
Objective: To examine trends and effects of weight loss treatment on health-related quality of life (HRQL) in the severely obese over 10 years. Design: Swedish obese subjects (SOS) intervention study is a controlled, longitudinal trial of the health effects of weight loss in the severely obese. Subjects: A total of 655 of 851 surgically treated and 621 of 852 conventionally treated obese men (body mass index, BMI greater than or equal to 34) and women (BMI greater than or equal to 38) who completed 10 years of the study. Measurements: HRQL was assessed before treatment and after 0.5, 1, 2, 3, 4, 6, 8 and 10 years. Results: HRQL change during the 10-year observation period largely followed phases of weight loss, weight regain and weight stability. Improvements and deteriorations in HRQL were associated with the magnitude of weight loss or regain, except regarding anxiety. Peak improvements in the surgical group were observed during the first year of weight loss, whereas the weight regain phase (mainly between 1 - and 6-year follow-up) was accompanied by a gradual decline in HRQL. The period from 6- to 10-year follow-up was characterized by relatively stable observations in both weight and HRQL. At 10 years, net gains were noted in all HRQL domains compared to baseline. Comparisons of treatment effects on HRQL in the surgical vs conventional group after 10 years showed significantly better outcome in the surgical group on current health perceptions, social interaction, psychosocial functioning and depression, whereas no significant differences were found for overall mood and anxiety. Long-term results of the study suggest that a maintained weight loss of about 10% is sufficient for positive long-term effects on HRQL, a limit that was reached in about two-thirds of the surgically treated patients who completed 10 years of the study. Conclusion: Long-lasting weight reduction in the severely obese has a general long-standing positive outcome on HRQL. Bariatric surgery is a favorable option for the treatment of severe obesity, resulting in long-term weight loss and HRQL improvements in a majority of patients. However, difficulties among some surgical patients to control and maintain weight loss over time should not be ignored. Future research should study if the long-term efficacy of bariatric surgery may be further enhanced by implementing lifestyle modification techniques in the postoperative management of patients.